2000
DOI: 10.1038/sj.ijo.0801115
|View full text |Cite
|
Sign up to set email alerts
|

Do African Americans have lower energy expenditure than Caucasians?

Abstract: OBJECTIVE: To review current studies that examine differences in energy expenditure between African Americans and Caucasians as possible modulators of attained differences in overweight status. DESIGN: Literature review of recent clinical and laboratory studies. METHODS: Studies chosen for review were those that examined directly resting metabolic rate (RMR), using indirect calorimetry, and total daily energy expenditure (TDEE) and physical activity energy expenditure (PAEE), using doubly labeled water. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 43 publications
(50 reference statements)
5
46
2
Order By: Relevance
“…These results are in agreement with several previous studies of nonsmokers which also found a lower rate of resting energy expenditure among black individuals compared to white individuals (Gannon et al, 2000). Collectively, these results suggest that black people have lower energy requirements than white people.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in agreement with several previous studies of nonsmokers which also found a lower rate of resting energy expenditure among black individuals compared to white individuals (Gannon et al, 2000). Collectively, these results suggest that black people have lower energy requirements than white people.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, much attention has focused on the potential contribution of physiologic variables such as resting energy expenditure (REE). Several studies have found a signi®cantly lower REE among black people compared to white people (Albu et al, 1997;Gannon et al, 2000;Jackic & Wing, 1998;Weyer et al, 1999). Considering that reduced REE is an important risk factor for weight gain (Ravussin & Swinburn, 1993;Ravussin et al, 1988), it is likely that an increased level of energy ef®ciency among black people plays an important role in ethnic differences in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic differences, for example in basal metabolic rates, could create weight differences even if there exists no differences in energy intake and expenditure. In a review of 15 studies, Gannon et al (2000) provide support for this explanation. They conclude that black women living in the U.S. may be particularly vulnerable to obesity due to a relatively lower energy expenditure for their metabolic size.…”
Section: Decomposition Resultsmentioning
confidence: 87%
“…Another possible explanation for the lower weight loss among African American subjects may lie in the lower REE that has been described for African Americans. African American children have lower REE than Caucasians [60][61][62][63][64][65][66][67] . In our study, not only was the REE of the African American subjects lower at baseline, the decrease in REE (adjusted for LBM and BFM) was 162 kcal/ 24 hr larger among African Americans than among Caucasians at 6 months, despite the fact that the African American subjects lost less weight.…”
Section: Discussionmentioning
confidence: 99%